Perancangan Aplikasi Pengamanan File Pada Memory Card Handphone Menggunakan Algoritma Kunci Asimetris Elgamal - Abdul Rahman (STMIK Budi Darma, 2019)
Issues Security and confidentiality of data is one important aspect in terms of information exchange. One solution to maintain security and confidentiality in the process of sending data is to use encryption as an encryption key in files. This study describes the development of cryptography (encryption and decryption) that applies the elgamal asymmetric algorithm. Elgamal algorithm was chosen because this algorithm is one of the asymmetric algorithms that are quite new. This research resulted in an application program aimed at preventing file security on external storage media in the form of mobile memory cards. In making this application, the method used is the Elgamal Asymmetric Key Algorithm, because it is very suitable for file security that results in the completion of the encryption and description process. This application was created with visual basic 2008 software and the creation of a file security application with encryption and description using an elgamal asymmetric algorithm, is expected to overcome these problems.